Impact of medication adherence on the efficacy of Baroreflex activation therapy - Ann‐Kathrin C. Schäfer; Dieter Müller; Ellen Born; Maria Mühlhaus; Stephan Lüders; Manuel Wallbach; Michael J. Koziolek (The Journal of Clinical Hypertension, 2022)
Abstract Therapy adherence significantly determines the success of antihypertensive therapy, especially in patients with resistant hypertension. Our study investigates the impact of drug adherence on the efficacy of Baroreflex‐activation‐therapy (BAT). In this retrospective analysis, the authors measured blood pressure (BP) and antihypertensive medication adherence (by gas chromatography‐mass spectrometry [GC‐MS] urine analysis) before and 6 months after BAT initiation. Adherence was defined as detection of ≥80% intake of prescribed medication at the time of follow‐up. Response to BAT was defined as BP drop ≥5 mmHg in systolic 24 h‐ambulatory BP (ABP) after 6 months. Overall patients (n = 38) median medication adherence was low, but rose from 60% (IQR 25%–100%) to 75% (IQR 38%–100%; p = .0194). After 6 months of BAT, mean systolic and diastolic office BP (‐21 ± 25 mmHg and ‐9 ± 15 mmHg; p < .0001 and .0004) as well as 24 h‐ABP dropped significantly (‐9 ± 17 mmHg and ‐5 ± 12 mmHg; p = .0049 and .0280). After 6 months of BAT, 21 patients (60%) could be classified as responders. There was neither significant difference in mean office systolic (‐21 ± 23 mmHg vs. ‐21 ± 28 mmHg; p = .9581) nor in 24 h‐systolic ABP decrease (‐11 ± 19 mmHg vs. ‐7 ± 15 mmHg; p = .4450) comparing adherent and non‐adherent patients. Whereas Antihypertensive Therapeutic Index (ATI) was unchanged in non‐responders, it significantly decreased in responders (from 50 ± 16 to 46 ± 16; p = .0477). These data are the first to show that BAT‐initiation leads to a clear BP reduction independently of patients´ medication adherence. Response to BAT is associated with a significant lowering of ATI, which might contribute to an underestimation of BAT efficacy.